(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
The main purpose of this article is to emphasize pronunciation training to improve speaking skills of Uzbek EFL(English as a Foreign Language) learners. It explains common phonetic difficulties caused by first language (L1) interference, presents effective pronunciation training techniques, and highlights the pedagogical significance of integrating pronunciation instruction into EFL classrooms. These suggest that targeted pronunciation training significantly improves intelligibility, fluency, confidence, and overall speaking performance among Uzbek EFL learners.